Classroom Behavior, Contexts, and Interventions Advances in Learning and Behavioral Disabilities Volume 25 - Cook, Bryan; Cook, Bryan; Tankersley, Melody; Landrum, Timothy J. (Emerald Group Publishing Limited, 2012)
The focus of this volume is to identify and review issues and outcomes associated with behavioral concerns of students with learning and behavioral disabilities. Students must navigate a number of environmental conditions, task demands, and social interactions with peers and adults throughout the school day. To be successful, they must employ a variety of learning and self-regulatory strategies, as well as meet teachers$1 (Bexpectations in the classroom. Students with learning and behavioral disabilities are more likely to fail in navigating the school day than nondisabled peers. Their failure is often associated with difficulties in some aspect of behavior. In this volume, internationally prominent scholars address contemporary topics such as grade retention, bullying and Harassment, response-to-intervention and universal systems in relation to how students with learning and behavioral disabilities are affected by them. Additionally, the scholars describe and discuss future directions for treatments such as social skills instruction, cognitive-behavioral prevention, social emotional learning programs, and self-monitoring. The volume is intended to be of interest to clinicians, teachers, researchers, graduate students, and others who work with students with learning and behavioral disabilities.s